2019
DOI: 10.1080/03067319.2019.1641202
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence- and FRET-based mercury (II) sensor

Abstract: A mercury (II) sensor has been proposed based on Fluorescence Resonance Energy Transfer (FRET) between N,N'-dioctadecyl thiacyanine perchlorate (NK) and Octadecyl rhodamine B chloride (RhB). Out of these two molecules NK is sensitive to Hg 2+ ions due to presence of sulfur atom in it. Accordingly, presence of Hg 2+ ions affects the NK fluorescence as well as FRET from NK to RhB. Our results showed that NK fluorescence intensity and FRET efficiency linearly decreases with increase in Hg 2+ ion concentration. Wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…The interaction of organic molecules with metal nanoparticles (NPs) is of central importance for a large number of applications in several fields, such as chemical and biological sensing [1][2][3][4], optics [5][6][7], energy [8][9][10][11], catalysis [12][13][14][15], and nanomedicine [16][17][18][19]. Many of these applications are based on the effect of the localized surface plasmon resonance (LSPR) on the absorption, emission, and scattering of molecules attached to or in close vicinity to the NP surface [20][21][22][23]. NPs have the remarkable property of strongly enhancing the local electromagnetic near-field [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction of organic molecules with metal nanoparticles (NPs) is of central importance for a large number of applications in several fields, such as chemical and biological sensing [1][2][3][4], optics [5][6][7], energy [8][9][10][11], catalysis [12][13][14][15], and nanomedicine [16][17][18][19]. Many of these applications are based on the effect of the localized surface plasmon resonance (LSPR) on the absorption, emission, and scattering of molecules attached to or in close vicinity to the NP surface [20][21][22][23]. NPs have the remarkable property of strongly enhancing the local electromagnetic near-field [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of dye quenching has been widely exploited for chemical and biological sensing applications, with one of the main techniques being fluorescence resonance energy transfer (FRET), in which the initially excited chromophore transfers its energy to an acceptor, thus quenching the fluorescence in the process [23,37,38]. In FRET, the donor and acceptor are molecules, and the energy transfer occurs via through space dipole-dipole interactions [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metal ions such as Hg +2 are also found in the water sample which makes it hard and causes health problems; hence, its detection is also important [ 148 ]. For this study, Jaba et al developed a FRET-based sensor for the detection of Hg +2 [ 149 ]. In this same work, the researchers used N, N-dioctadecyl thiacyanine perchlorate, i.e., NK, as a donor and octadecyl rhodamine B chloride, i.e., RhB, as an acceptor.…”
Section: Applications Of Fret Biosensormentioning
confidence: 99%
“…Firstly, they introduced both molecules in thin film using Langmuir–Blodgett (LB) and in spin coating (SC), and after that, both were dipped into Hg +2 solution, i.e., sample solution. After performing spectroscopic analysis, they found detection of Hg +2 with detection limit of 9.13 ppb in LB and 11.7 in SC films [ 149 ].…”
Section: Applications Of Fret Biosensormentioning
confidence: 99%
“…Nanomaterials such as AuÀ NPs and Au-nanorods have been functionalized with rhodamine B (RhB) for mercury detection. [132][133][134] It was observed that various fluorescencebased sensors modulate their fluorescence resonance energy transfer (FRET) between the molecules such as RhB/AuÀ NPs system (Figure 10), [132] and RhB/N,N'-dioctadecyl thiacyanine perchlorate system, [135] when detecting Hg 2 + ions in an aqueous solution.…”
Section: R E V I E W T H E C H E M I C a L R E C O R Dmentioning
confidence: 99%